Clinical and epidemiological features and dental care need of patients attended at Estomatología de Pacientes Espe- ciales in a period of 2 years - García Murga, José Antonio (2020)
Objective: Determine the clinical and epidemiological characteristics and need for dental care in the population of special patients that received attention in EPE – CEC – UPCH since April from 2016 to March 2018. Material and Methods: We analyze variables, such as the origin, gender, age, systemic diagnoses and need for treatment through descriptive statistics. Results: The sample were 1735 clinical ﬁles that met the inclusion criteria. The 87.9% live in Lima city and 63% in the northern zone, 62.2% were female and 37.8% male. The average age was 52.97 ± 25.92 years old, and 50.26% were older than 60 years. Special patient has 1.97 ± 1.21 systemic diagnoses, with a higher prevalence of circulatory system diseases with 35.5% followed by endocrine, metabolic and nutritional diseases with 26.4%. Regarding the need for dental care, the main treatments were dental restorations (75%), oral rehabilitation (59.4%), and dental surgery (36.7%). Conclusions: Most part of the special population attended, came from the northern zone of Lima city, was female gender and belonged to the older adult group. In addition, the most prevalent diseases were arterial hypertension (29.51%) and diabetes mellitus (14.98%); and the main treatments were dental restorations and oral rehabilitation.